SIMULASI GERAK DAN ANALISIS KESTABILAN KOPLING INERSIA WAHANA DIRGANTARA DENGAN BENTUK BADAN RAMPING - Muhammad, Hari; Samputra, Hilman; Jenie, Yazdi I; Sembiring, Javensius (Indonesian Journal of Aerospace, 2011)
Inertia coupling is a motion phenomenon of a high-speed airplane having slender body and low aspect ratio. This inertia coupling happens when the aircraft performs a roll manoeuvre motion with a high roll rate. This paper will discuss the derivation of inertia coupling equations of motion, modelling equations of motion in the Matlab/Simulink software, simulating the dynamics motion, and analyzing the stability of the inertia coupling. Numerical simulation and stability analysis of the inertia coupling for a fighter aircraft will be presented in this paper.